ANALISA KINERJA LALU LINTAS JALAN JENDERAL AHMAD YANI KOTA PALEMBANG - Agustini, Marice; Septriansyah, Verinazul; Sutama, Adji; Fitriana Umari, Zuul; Delima Amanda Putri, RAS (Universitas Muhammadiyah Palembang, 2024)
Traffic performance refers to the evaluation of the service quality of a road segment relative to the traffic flow through it. Road traffic performance assessment is measured by the degree of saturation and travel speed. Road capacity (C) is the ability of a road section to accommodate traffic flow in a certain time unit. Road capacity is influenced by the type of side obstacles and the frequency of occurrence. This research was conducted on Jalan Jenderal Ahmad Yani Campus A, Muhammadiyah University of Palembang to calculate road capacity (C) and traffic performance on Jalan Jenderal Ahmad Yani. Data analysis was carried out using the 2023 Indonesian Road Capacity Guide where road capacity and degree of saturation are road traffic performance parameters so that the value of the level of service is known. Based on the results of research and analysis that has been carried out located on Jalan Jenderal Ahmad Yani, Palembang, the road capacity (C) is 2,924 PCU/hour and the free flow speed (VB) value is 49.59 Km/hour, while the road traffic performance and level of service on the Jalan Simpang 4 Jakabaring-Jalan Jenderal Ahmad Yani section is 0.81 and is classified as category D (Flow is close to stable, speed can still be controlled, traffic volume is approaching capacity), while from the direction of Jalan Jenderal Ahmad Yani -Intersection 4 Jakabaring obtained a service level of 0.94 and was classified as category E (Unstable flow and sometimes stopping, traffic volume approaching capacity, low speed and changing).